2018
DOI: 10.1002/ejp.1303
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and neuropathic pain conditions do not primarily evoke anxiety‐like behaviours in C57BL/6 mice

Abstract: Anxiety-like behaviour is not primarily altered following CFA and SNI in C57BL6 mice, irrespective of the gender, mouse sub-strain, housing conditions or affected body side within the herein investigated time period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 90 publications
1
47
1
1
Order By: Relevance
“…Similar to rats, a single study found no depression-like behavior in the forced swimming test from the 3rd to 97th day following the SNI surgery in mice. Interestingly, this same study did not even detect anxiety-like behaviors under the same time point and pain conditions [52].…”
Section: Behavioral Symptoms Associated With the Spared Nerve Injurymentioning
confidence: 74%
See 2 more Smart Citations
“…Similar to rats, a single study found no depression-like behavior in the forced swimming test from the 3rd to 97th day following the SNI surgery in mice. Interestingly, this same study did not even detect anxiety-like behaviors under the same time point and pain conditions [52].…”
Section: Behavioral Symptoms Associated With the Spared Nerve Injurymentioning
confidence: 74%
“…In the open field, no anxiety-like behavior was observed on day 7 [28], from day 3 to week 7 [12] and from day 3 to week 14 [52] after the SNI. Urban et al [12] also found a lack of anxiety-like behavior in the elevated zero-maze and marble-burying while Pitzer et al [52] in the elevated plus-maze and hole board. It is certainly not easy to understand the reason for this inconsistency.…”
Section: Behavioral Symptoms Associated With the Spared Nerve Injurymentioning
confidence: 85%
See 1 more Smart Citation
“…1A-E. Overall, repeated measures (RM) ANCOVA with second/last pre-surgical baseline as covariate, demonstrated overall significant effects of strain (F [4,74] = 5.697, P < 0.0001), surgery (F [1,74] = 166.3, P < 0.0001), and a strain*surgery interaction (F [4,74] = 8.639, P < 0.0001), indicating that the effect of surgery was not similar for all strains. We therefore performed two-way RM ANOVA for each individual strain, and found the effect of surgery to be significant for all strains, except for the Lewis strain (F F344/ICO [1,330] = 94.24, P < 0.0001.…”
Section: Development Of Mechanical Allodynia Following Nerve Injury mentioning
confidence: 88%
“…Human studies have shown a positive correlation between DED severity and symptoms of anxiety 7,[60][61][62] . While there have been some reports of increased signs of anxiety in chronic pain models, other reports have not found a significant effect of pain on anxiety measures [63][64][65][66][67][68][69][70] . Using the elevated plus maze, single LGE reduced open arm time only in female mice, whereas double LGE reduced open arm time in both female and male mice.…”
Section: Discussionmentioning
confidence: 92%